Overexpression of TRAF4 promotes lung cancer growth and EGFR‐dependent phosphorylation of ERK5. Issue 10 (17th August 2022) - He, Siwei; Dong, Danfeng; Lin, Jiafei; Wu, Beiying; Nie, Xiaomeng; Cai, Gang
Abstract : Tumor necrosis factor receptor‐associated factor 4 (TRAF4) is overexpressed in a variety of carcinomas of different origins, but its role in tumorigenesis remains incompletely understood. Previous studies suggest that TRAF4 promotes epidermal growth factor receptor (EGFR) activation in non‐small cell lung cancer (NSCLC). However, the downstream signaling pathway of TRAF4‐mediated EGFR activation, as well as its effects on tumor cells, have not been fully elucidated. Here we report that TRAF4 overexpression is associated with increased activity of extracellular signal‐regulated kinase 5 (ERK5) in NSCLC tissues. Activation of ERK5 was dependent on TRAF4‐mediated EGFR activation, since inhibition of either TRAF4 or EGFR dramatically abolished phosphorylation of ERK5. Mechanistically, EGFR recruited mitogen‐activated protein kinase kinase kinase 3 (MEKK3), an upstream kinase of ERK5, in a TRAF4‐dependent manner. Thus, our data suggest that an EGFR‐TRAF4‐MEKK3‐ERK5 axis promotes the proliferation of tumor cells, and this may be a potential target for therapeutic intervention of NSCLC. Abstract : In this study, an EGFR‐TRAF4‐MEKK3‐ERK5 axis in tumor cells was revealed to promote the uncontrollable proliferation of tumor cells. This pathway was activated in non‐small cell lung cancer tissues, but not in normal lung tissues.